A Dose-Effect Study of Cisplatin Ototoxicity in Albino Guinea Pigs - Salehi, Negin (Iran J Otorhinolaryngol, 2020)
INTRODUCTION: Cisplatin is one of the most commonly used antineoplastic drugs; nonetheless, its ototoxic dose-limiting side effects have remained a significant challenge in clinical practice. The recognition of the exact template of hearing loss induced by multiple low doses of cisplatin could be of great help in managing the treatment process. The present study aimed to investigate the effects of multiple doses of this drug on the auditory system. MATERIAL AND METHODS: The present study was performed using an experimental guinea pig model in four groups as follows:1- 0.9% sodium chloride solution, 2- total dose of 7.5 mg/kg Cisplatin, 3- total dose of 10 mg/kg Cisplatin, and 4- total dose of 12.5 mg/kg cisplatin. The drugs were injected as 2.5 mg/kg/daily IP access in all groups. The auditory brainstem response (ABR) test was performed before the treatment and after every injection on a daily basis up to 72 h after the last injection. RESULTS: There was dose-dependent significant hearing loss in all evaluated frequencies in three cisplatin groups. The general template of induced hearing loss during experimental days was almost the same in groups Cis7.5 and Cis10. In Cis 12.5 group, there was a jump in the threshold shift on the 5th day of the experiment and an upward trend in the function. CONCLUSION: As evidenced by the obtained results, the monitoring of hearing loss after every injection in patients who receive the drug and detecting the exact dose-dependent pattern of the induced hearing loss is of great help in controlling its undesirable destructive side effects on the auditory system.